INHIBITING HEPATITIS B VIRUS GENE EXPRESSION WITH HAMMERHEAD RIBOZYMES THAT TARGET THE HBx OPEN READING FRAME - Weinberg, Marc Saul (My University, 2002)
Hepatitis B virus (HBV) infection is endemic to several populous regions and is often complicated by cirrhosis and hepatocellular carcinoma (HCC). Present treatment of chronic HBV infection is usually ineffective and novel therapeutic approaches are an important medical objective. The X open reading frame (ORF) of HBV, HBx, is a conserved sequence that overlaps with the polymerase ORF and viral c/'s-elements, and is present within all viral transcripts. In addition, the HBx ORF encodes a 17 kDa transactivator protein, HBx, which is required for the establishment of viral infection and has been implicated in HBV-associated hepatocarcinogenesis. The HBx sequence thus represents a compelling target for applying nucleic acid hybridisation-based therapeutic agents for the inhibition of HBV gene expression and replication.
A thesis submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Doctor of Philosophy Johannesburg, 2002
Keywords: Hepatitis B virus; Ribozyme, hammerhead; hepatitis B virus-encoded X